Optimizing Project Management using Artificial Intelligence (European Journal of Formal Sciences and Engineering, 2022)
This study focuses on on identifying the weakest points of project management and the possibility of where artificial intelligence can help precisely in their optimization. The results were taken from a survey where project managers of various categories were asked about the main challenges facing management today and the points where artificial intelligence can be seen as a optimization tool. In this decade, artificial intelligence (AI) has undoubtedly been one of the most influential technologies. AI has changed the way people live and work, and project management is no exception. There is always controversy about the use of AI technology. In this paper first is explained the need for companies to use AI technology and after considering the advantages and risks of AI. Also using project management based on machine learning is the optimal option. Some proposals for the implementation of AI in project management are presented. The study describes how AI systems can support project managers to become more efficient in their work.
Keywords: Optimization, Technology, Management, Project Management, Artificial Intelligence.